Determination of consistent semiempirical one-centre integrals based on coupled-cluster theory. (4th March 2017) - Margraf, Johannes T.; Claudino, Daniel; Bartlett, Rodney J.
ABSTRACT: We examine the one-centre integrals used in semiempirical molecular orbital theory, for the elements H–Ne. The currently used parameters do not provide good estimates for the relative energies of ionised states of atoms. Directly calculating the one-electron integrals U ss and U pp with coupled-cluster theory and fitting the two-electron repulsion integrals G ss and G pp to accurate coupled-cluster ionisation curves improves this behaviour. Since all the remaining parameters can be derived from these, the number of fitted variables is reduced from seven to two. The two-parameter model provides qualitative agreement with coupled-cluster theory for all ionisation potentials (IPs) and the principal electron affinity (EA). To obtain quantitative agreement for the principal IP and EA, U ss and U pp are included as variables in a four-parameter model. We discuss the new parameters and implications for the development of new, consistent semiempirical Hamiltonians. GRAPHICAL ABSTRACT: